Beyond the A‐layer: adsorption of lipopolysaccharides and characterization of bacteriophage‐insensitive mutants of Aeromonas salmonicida subsp. salmonicida. Issue 2 (4th June 2019) - Paquet, Valérie E.; Vincent, Antony T.; Moineau, Sylvain; Charette, Steve J.
Summary: Aeromonas salmonicida subsp. salmonicida is a fish pathogen that causes furunculosis. Antibiotherapy used to treat furunculosis in fish has led to resistance. Virulent phages are increasingly seen as alternatives or complementary treatments against furunculosis in aquaculture environments. For phage therapy to be successful, it is essential to study the natural mechanisms of phage resistance in A. salmonicida subsp. salmonicida . Here, we generated bacteriophage‐insensitive mutants (BIMs) of A. salmonicida subsp. salmonicida, using a myophage with broad host range and characterized them. Phage plaques were different depending on whether the A‐layer surface array protein was expressed or not. The genome analysis of the BIMs helped to identify mutations in genes involved in the biogenesis of lipopolysaccharides (LPS) and on an uncharacterized gene ( ASA_1998 ). The characterization of the LPS profile and gene complementation assays identified LPS as a phage receptor and confirmed the involvement of the uncharacterized protein ASA_1998 in phage infection. In addition, we confirmed that the presence of an A‐layer at the bacterial surface could act as protection against phages. This study brings new elements into our understanding of the phage adsorption to A. salmonicida subsp. salmonicida cells. Abstract : When the phage receptor, the lipopolysaccharide (LPS), is not covered by the A‐layer (A), an outer membrane protein found on A. salmonicida subsp salmonicida bacterium, the bacteriophage binds to its host cell and initiates its lytic cycle.